Stakeholders’ Contribution in the Management of Secondary Education for Sustainable Development in Rivers State (International Journal of Educational Management, Rivers State University., 2025)
The study investigated stakeholders’ participation in the management of secondary education for sustainable development in Rivers State. The study which adopted descriptive survey research design was guided by two research questions and two hypotheses. The population of the study consisted of 552 principals and PTA chairmen in the 276 public secondary schools in Rivers State. A sample of 112 principals and PTA chairmen representing 20% of the population was drawn through proportionate stratified random sampling technique. A questionnaire entitled: “Stakeholders Participation in the Management of Secondary Education for Sustainable Development Questionnaire (SPMOSESDQ)” developed by the researcher was used for data collection. The instrument which contained 20 items was properly validated and the test of reliability yielded 0.88 through Cronbach Alpha method. Mean, mean set, rank order and standard deviation were used to analyse the research questions, while z-test was used to test the hypotheses at 0.05 level of significance. The results of the study showed that stakeholders participate in the management of secondary education through: construction of required building facilities; provision of ICT facilities; perimeter fencing of school premises; donation of books; and award of scholarships among others. The study also revealed that the challenges of stakeholders’ participation in the management of secondary education include among others: poor school-community relationship; ignorance, inadequate information and coordination of stakeholders. Based on the findings, conclusion was drawn and the following recommendations among others were made: secondary school administrators should maintain effective communication with secondary education stakeholders, and school administrators should be prudent, transparent and accountable in order to encourage stakeholders’ participation in the management of secondary education in Rivers State.